Antibacterial and anticancer activity of hydrothermally-synthesized zinc oxide nanomaterials using natural extracts of neem, pepper and turmeric as solvent media. (30th April 2020) - Abinaya, C; Manjula Devi, R; Suresh, P; Balasubramanian, N; Muthaiya, N; Kannan, N D; Annaraj, J; Shanmugaiah, V; Pearce, J M; Shanmugapriya, P; Mayandi, J
Abstract: A novel and simple wet chemical hydrothermal synthesis method was employed in the preparation of zinc oxide (ZnO) nanoparticles using neem (N), pepper (P) and turmeric (T) extracts as solvent media. The structural and optical properties as well as the antibacterial and anticancer properties of all the samples (ZnO, N/ZnO, P/ZnO, T/ZnO and NPT/ZnO) were characterized and analyzed. Solvent media was found to have an effect on both the size and the morphology of the nanoparticles, which in turn effected their optical and cytotoxic properties. The colony forming unit (CFU) assays were done for E. coli, S. aureus and S. typhi in which T/ZnO (∼2) and P/ZnO (∼3) showed a remarkable effect on S. aureus for 100 μ g ml −1 and nearly zero for 150 μ g/ml. The zone of inhibition (ZoI) was measured for S . agalactiae, S. dysgalactiae and S. pyogenes .The results showed that S. dysgalactiae is more sensitive to N/ZnO.Finally, the anticancer properties of these compounds towardsprostate cancer cells was investigated. Among the active compounds T ZnO showed the highest activity with low IC50 value (37.751 μ g/ml) followed by P ZnO (45.68 μ g ml −1 ).